Offshoring, reshoring y nearshoring: Nuevas tendencias en los mercados ecuatorianos; Offshoring, reshoring and nearshoring: New trends in the Ecuadorian markets - Jonella-Abigail Guzmán Armijos; Sandra-Sayonara Solorzano Solorzano; Irene-Patricia Sánchez González (Atlantic Review of Economics (ARoEc), 2021)
– Introduction: The new globalization process represents a constant challenge for companies, testing their ability to respond and adapt to new scenarios, this includes the internationalization of the various logistics value chains. In these times of competitiveness and productivity, companies are forced to investigate new ways of producing their goods or services, new markets that are attractive and sustainable over time, which allow extending the production process as well as reducing costs, improving traceability in the logistics chain in order to propel economies in the market to meet new demands. Objective: This research aims to analyze new trends in the markets through the study of offshoring, reshoring and nearshoring, and the impact on the logistics value chains of the Ecuadorian markets, of the SMEs of the Province of El Oro for their process of internationalization, through the aforementioned constructs. Methods: Theoretical and empirical methods such as historical-logical, analytical-synthetic and inductive-deductive were used for the collection of information on small and medium- sized enterprises using secondary sources such as databases or journals, to proceed with the respective analysis. on the implementation of new trends considered as a viable opportunity for participation in the international market. Results: The main results indicate that SMEs constitute one of the main sources of income and employment for the Ecuadorian economy, in such a way that the economic sectors that have a greater contribution are those of service and commerce. For this reason, the province of El Oro is in fifth place with the highest participation in total sales equivalent to 3.09%, so that by implementing these offshoring, reshoring and nearshoring strategies, they would increase their expansion in global markets, contributing significantly in the various production and marketing processes. Conclusions: These strategies allow small and medium-sized Ecuadorian companies to outsource their facilities to enter new markets, which is why the adaptation of a good logistics network is established as essential in such a way that the product acquires value, being key to guarantee the competitiveness of the companies. SMEs, given that they are considered as sources of progress within the economy due to their great growth potential, that is, to produce a traction effect on the development of the private sector. The limitations faced by SMEs in the province of El Oro are the scarce business knowledge, the lack of implementation of technology for the production process and the money or solvency to grow, for this reason the most appropriate alternatives must be known to face the great competitions of the globalized market.
Keywords: 330; Offshoring; reshoring; nearshoring; value chain